2003
DOI: 10.1021/jf0346354
|View full text |Cite
|
Sign up to set email alerts
|

Rugged LC-MS/MS Survey Analysis for Acrylamide in Foods

Abstract: The described liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for the detection of acrylamide in food entails aqueous room temperature extraction, SPE cleanup, and analysis by LC-MS/MS. The method is applicable to a wide variety of foods. [(13)C(3)]acrylamide is the internal standard. The limit of quantitation is 10 ppb (microg/kg). Data were obtained in duplicate from >450 products representing >35 different food types. The variability in analyte levels in certain food types suggests that it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
115
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(126 citation statements)
references
References 16 publications
9
115
0
2
Order By: Relevance
“…Although robust methods have been reported (Roach et al 2003;Croft et al 2004) that can achieve good sensitivity and selectivity of acrylamide for practically all of the relevant food matrixes, the present authors also found that chocolate products are troublesome matrixes, and that selected mass transitions reveal a difficulty in obtaining baseline separation in certain profiles (Roach et al 2003). In addition, multiple responses are observed in each of the mass transitions at a different retention time but close to that of acrylamide, which may cause interference.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Although robust methods have been reported (Roach et al 2003;Croft et al 2004) that can achieve good sensitivity and selectivity of acrylamide for practically all of the relevant food matrixes, the present authors also found that chocolate products are troublesome matrixes, and that selected mass transitions reveal a difficulty in obtaining baseline separation in certain profiles (Roach et al 2003). In addition, multiple responses are observed in each of the mass transitions at a different retention time but close to that of acrylamide, which may cause interference.…”
Section: Introductionmentioning
confidence: 57%
“…However, MS/MS data obtained from low-mass parent ions are subject to interference and can be misleading in the absence of sufficient internal standard data. Therefore, MS/MS analysis for acrylamide requires a prior chromatographic separation of the analyte from co-extractive materials and unambiguous identification of the analyte under the conditions of analysis by comparison of the analyte response to that of the internal standard (Roach et al 2003). Meanwhile, MS/MS analysis of chocolate samples are challenging because of coextractives that make it through the clean-up steps and the inherent difficulties in confirming a low molecular mass compound in a complex matrix using mass spectrometry.…”
Section: Optimization Of Lc-esi-ms/ms Conditionsmentioning
confidence: 99%
“…Gas chromatography, liquid chromatography, GC-MS (Surma, Sadowska-Rociek, Cieślik & Sznajder-Katarzyńska, 2017;Ono et al, 2003;Biedermann et al, 2002) and LC-MS ( Khan et al, 2017;Becalski, Lau, Lewis & Seaman 2003;Roach, Andrzejewski, Gay, Nortrup & Musser, 2003;Zyzak et al, 2003) are used most often. The acrylamide contents are different in some commercial coffee from several manufactures in different countries, with 42-338 ng g -1 in instant coffees and about 50ng g -1 in filtered coffee.…”
Section: Determination Of Acrylamide In Coffeementioning
confidence: 99%
“…On the other hand, okara is richer in reducing sugar than wheat flour: our okara sample has 3.83 g/100g of reducing sugar while the average content of reducing carbohydrates in wheat flour was 1.7 g/100g 28 .…”
Section: Formation Of Maillard Reaction Products In Biscuits Added Wimentioning
confidence: 66%
“…Specifically, the use of auxiliary gas coupled to a capillary voltage higher than 4.0 kV caused the fragmentation of acrylamide in source. As a consequence it was decided to use an auxiliary gas flow rate of 6 AU in order to avoid undesired fragmentation of the molecules and the formation of the typical fragment (72→55) [26][27][28]34 . The lens voltage was optimized setting the mass …”
Section: Methods Developmentmentioning
confidence: 99%